Impact of Shiftwork on Irritable Bowel Syndrome and Functional Dyspepsia - Kim, Hye In (The Korean Academy of Medical Sciences, 2013)
Disturbances in biological rhythms could lead to unfavorable health impact. This study aimed to evaluate the prevalence of functional dyspepsia (FD) and irritable bowel syndrome (IBS) in rotating shift workers, and to determine the factors that have significant association with the prevalence of FD and IBS. The research had been carried out among nurses and nursing assistants working at Ewha Womans University Mokdong Hospital between December 2010 and February 2011. The subjects completed self-reported questionnaires, including the quality of the sleep and the level of stress. The prevalence of FD and IBS defined by ROME III criteria, and factors associated the disorders in rotating shift workers were compared with those of day workers. A total of 207 subjects were included in the study with 147 rotating shift workers (71.0%), and 60 (29.0%) day workers. The prevalence of IBS in rotating shift workers was higher than that in day workers (32.7% vs 16.7%, P = 0.026). However, no significant difference in the prevalence of FD was observed between the two groups (19.7% vs 20.0%, P = 0.964). In the multivariate analysis, the risk factors for IBS were rotating shift work (OR, 2.36; 95% CI, 1.01-5.47) and poor sleep quality (OR, 4.13; 95% CI, 1.82-9.40), and the risk factors for FD were poor sleep quality (OR, 2.31; 95% CI, 1.01-5.28), and severe stress (OR, 2.19; 95% CI, 1.06-4.76). A higher prevalence of IBS among rotating shift workers could be directly associated with the circadian rhythm disturbance. The circadian rhythm disturbance may be related with the pathogenesis of IBS.